Plantain: plant more, pick more - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
'Such an intensive production system is the way of the future if our countries are to meet the ever-increasing demand of the urban middle class for plantain.' That is a major conclusion of a study visit by eight farmers, extension officers and...